2011
DOI: 10.4236/jep.2011.27115
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Natural Uranium in the Ground Water around Jaduguda Uranium Mining Complex, India

Abstract: Ground water ecosystem surrounding the uranium processing facility at Jaduguda, India has been studied for natural uranium distribution. Annual intake of uranium through drinking water for members of public residing around the uranium complex is found to be in the range of 41.8 Bquy<sup>–1</sup> - 44.4 Bquy<sup>–1</sup>. The intake and ingestion dose is appreciably low (<2 Sv.y<sup>–1</sup>) which is far below the WHO recommended level of 100 uSv.y<sup>–1</sup>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Sahoo et al, has been reported U concentration in the range of 0.1-19.6 lg l -1 in the drinking water samples collected from Orissa, Andhra Pradesh, Maharashtra, Madhya Pradesh, Kerala etc. [13], U concentration around uranium mining and processing facility of the Jaduguda, Jharkhand has been reported in the range of 0.5-28 lg l -1 [15] and around Narwapahar U mine in Jharkhand it has been in the range of 0.1-3.75 lg l -1 [14]. Further around the proposed U mining sites located at Lambapur and Pedagattu in the Nalgonda district of Andhra Pradesh, it has been reported in the range of 0.2-77.4 lg l -1 [18].…”
Section: Comparison Of U Concentration With Worldwide Valuesmentioning
confidence: 98%
See 2 more Smart Citations
“…Sahoo et al, has been reported U concentration in the range of 0.1-19.6 lg l -1 in the drinking water samples collected from Orissa, Andhra Pradesh, Maharashtra, Madhya Pradesh, Kerala etc. [13], U concentration around uranium mining and processing facility of the Jaduguda, Jharkhand has been reported in the range of 0.5-28 lg l -1 [15] and around Narwapahar U mine in Jharkhand it has been in the range of 0.1-3.75 lg l -1 [14]. Further around the proposed U mining sites located at Lambapur and Pedagattu in the Nalgonda district of Andhra Pradesh, it has been reported in the range of 0.2-77.4 lg l -1 [18].…”
Section: Comparison Of U Concentration With Worldwide Valuesmentioning
confidence: 98%
“…Taking the geometric mean of the measured U concentration, the annual effective dose due to intake of only U through drinking water pathway to the member of the public was estimated to be 16.75 l Sv year -1 , which is found to be well below the recommended dose limits of 100 l Sv year -1 as per WHO [21] and it is about 5.6 % of the global average annual ingestion dose [6]. In India, [13][14][15] reported mean annual ingestion doses in the different parts of the country are 3.5, 0.99 and 2 l Sv year -1 , respectively which are slightly less in comparison to the present study.…”
Section: Assessment Of Annual Effective Dosementioning
confidence: 99%
See 1 more Smart Citation
“…The estimation of uranium in the plant, soil, mill tailing and water samples was carried out by UVFluorometer following the processing of the samples by Sethy et al (2011. The emitted fluorescence intensity of 5,546A° that is unique for uranium was measured using a UV-Fluorimeter (Electronics Corporation of India Limited, Hyderabad Model: FL6224A) with an excitation wavelength 3,650A°. The intensity of fluorescence is directly proportional to the quantity of uranium present in the sample.…”
Section: Uranium Estimationmentioning
confidence: 99%
“…The Jaduguda mine has been the site of uranium mining and milling for more than four decades (Sethy et al, 2011), operating since 1967 providing the basic raw material required to cater the energy requirement of the country (Sarangi, 2003). The uranium mill tailing ponds at Jaduguda and Turamdih receive processed waste from ores mined at the six mine stations at Jharkhand namely Jaduguda, Bagjata, Bhatin and Turamdih, Narwapahar, Banduhurang.…”
Section: Introductionmentioning
confidence: 99%